Changes in Microbiota Across Developmental Stages of Aedes koreicus, an Invasive Mosquito Vector in Europe: Indications for Microbiota-Based Control Strategies - Alfano, Niccolò; Tagliapietra, Valentina; Rosso, Fausta; Manica, Mattia; Arnoldi, Daniele; Pindo, Massimo; Rizzoli, Annapaola (Frontiers in Microbiology, 2019)
Since it has been understood that gut microbiota of vector mosquitoes can influence their vector competence, efforts have been undertaken to develop new control strategies based on host microbiota manipulation, and aimed at suppressing the vector population or replacing it with a less competent one. For the proper design of such control strategies it is necessary to know the microbiota composition of the target vector species, how it is acquired, and how it changes throughout the host’s life cycle. In this study, 16S rRNA amplicon high-throughput sequencing was used to characterize the changes in microbiota from the aquatic environment (larval breeding sites) to the different developmental stages of field-collected Aedes koreicus in Italy, an emerging invasive mosquito species in Europe and a potential vector of several pathogens. The bacterial communities of the aquatic breeding sites, larvae, pupae and adults showed distinctive structures to one another. Indeed, 84% of community members were unique to a given sample type. Nevertheless, almost 40% of the sequences generated were assigned to bacteria detected in all sample types, suggesting the importance of bacteria transstadially transmitted from water to the adult stage in constituting mosquito microbiota. Among these, genus C39 largely constituted water microbiota, family Burkholderiaceae was the most abundant in larvae and pupae, and genus Asaia dominated adult communities. In addition, Asaia consitituted a core microbiota across all sample types. Our results suggest that the microbiota of Ae. koreicus mosquitoes is composed by a community which derives from the aquatic bacteria of the larval breeding sites, is then filtered by the larval gut, where only certain members are able to persist, rearranged by metamorphosis and finally modified by the change in diet at the adult stage. Understanding how the microbiota of Ae. koreicus changes through the mosquito life cycle represents a first step in selecting bacterial candidates for use in microbiota-based intervention measures for this species. The properties which Asaia exhibits in this species, such as dominance, high prevalence and transstadial transmission, prevent the use of Wolbachia but make Asaia an ideal candidate for paratransgenesis.